Recreational fisheries target declining populations of brown trout (Salmo trutta L.) in Northern Norway as revealed by a genome wide array of SNP markers - Schmidt, Simon Nordblad (UiT Norges arktiske universitet, 2019)
Marine recreational and commercial exploitation of salmonids often target a mixed stock consisting of genetically distinct and independent populations with varying abundances, life histories, standing genetic variation, and conservation status. In this study we use SNP markers to investigate the genetic population structure of juvenile brown trout (Salmo trutta L.) from five distinct watercourses in order to identify the contribution of different source populations in a mixed stock fishery on sea-run brown trout. We identify significant genetic population structure between the watercourses, even between those with little geographical separation. While the Saltdal watercourse in recent years has seen a decline in brown trout catchments, we discover that it is the main contributor to the mixed stock; supplying 63% of sea-run brown trout longer than 50 cm and 76% longer than 70 cm. Sea-run brown trout shorter than 50 cm mainly exhibited genetic patters dissimilar to those of our reference populations. For a holistic view of the sea-run brown trout fisheries and to obtain a better understanding of the dynamics of the fjord system, further research is therefore warranted.